2001
DOI: 10.1097/00006676-200105000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Intraductal Papillary Mucinous Tumors of the Pancreas Based on Imaging Findings

Abstract: The aim of this study was to assess the imaging findings of pathologically proven intraductal papillary-mucinous tumors of the pancreas and the natural history of follow-up cases, and to optimize the therapeutic management of patients with these tumors according to their imaging findings. All nine patients with main duct type tumors were histologically diagnosed as having adenocarcinoma or adenoma, with no hyperplastic lesion. The images failed to discriminate between the two histologic types. In 26 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 11 publications
1
24
2
Order By: Relevance
“…A combination of peroral pancreatoscopy and intraductal ultrasonography resulted in a considerably improved differential diagnosis of malignant and benign IPMT and was useful for determining an effective therapeutic approach. 11,12 Recently some reports have encouraged the establishment of molecular diagnosis by using K-ras, p53, p16(INK4A), Smad4, telomerase activity, and the expression of MUC1. [13][14][15][16][17][18] However, these techniques are not yet practically useful.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of peroral pancreatoscopy and intraductal ultrasonography resulted in a considerably improved differential diagnosis of malignant and benign IPMT and was useful for determining an effective therapeutic approach. 11,12 Recently some reports have encouraged the establishment of molecular diagnosis by using K-ras, p53, p16(INK4A), Smad4, telomerase activity, and the expression of MUC1. [13][14][15][16][17][18] However, these techniques are not yet practically useful.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports in the English literature on identifying predictors of malignancy in asymptomatic mucinous lesions [22] . There have been four reports in the English literature describing the natural history of pancreatic IPMN evaluated by ERCP, CT or MRCP [81][82][83][84] .…”
Section: Methods Of Follow-upmentioning
confidence: 99%
“…Some researchers have reported that resection should be performed whenever IPMNs are diagnosed, even if they are considered to be benign by the imaging findings, 10 whereas others reported that no enlargement of the IPMNs occurred during several years of follow-up 19,20 and longterm survival could be expected in some patients without a resection. 21 Our results suggest that benign IPMNs should be strictly followed up without resection because IPMNs generally progress slowly, occur in elderly patients, and sometimes occur multifocally, thus leading to an extensive resection and higher postoperative morbidity.…”
Section: Commentmentioning
confidence: 99%